Analyzing the Impact of Administrative District, Urban Planning Zone, and Purpose of Building on Coworking Spaces and Flexible Workspaces—A Case Study of Sofia, Bulgaria - Ivanka G. Kamenova (Buildings)
This article provides an overview of coworking spaces and flexible workspaces in Sofia Municipality, Bulgaria. The study aims at examining whether the type of urban plan zone, the particular municipal administrative district, and the purpose of the building in which they are located have an impact on such modern workspaces. Existing spaces in the municipality were counted and classified according to the following criteria: origin of the operators, accessibility, level of specialization, purpose of the hosting building, location in a particular district, and urban planning zone. The average rent for Hot desk, Dedicated desk, Private office, and Virtual office was calculated for the territory determined by the research. The findings demonstrate that the number of coworking and flexible workspaces is influenced by the type of urban planning zone, the municipal administrative district, and the purpose of the building. The study also revealed that the majority of such spaces are concentrated in the zone of the old town center or in a mixed multifunctional zones and are located in administrative, business buildings.